The Prevalence and Distribution of Domiciliary Cockroaches in Rural Areas: A Cross-Sectional Study Design in Limpopo Province - Mapula Luckyjane Molewa; Tobias George Barnard; Nisha Naicker (Masters Program in Public Health, 2024)
Background: Cockroach infestation raises health concerns in the communities. The study aimed to identify the type of cockroach species found in the rural parts and assess the distribution of cockroach species in the area.Subjects and Method: A descriptive cross-sectional study was conducted in the households found in Ward 2 villages, Bolobedu and Limpopo Province in March 2021. A total of 120 households were selected using a multistage sampling strategy. Structured interviews were conducted to gather information about cockroach infestation in the households. The variables of interest in this study included the locations of cockroach sightings, pest control strategies used, and cockroach species trapped. A total of 1,186 cockroaches were trapped using a size 21×15 cm2 sticky paper sheet. Data analysis was done using SPSS version 29.Results: About 751 (64%) of cockroaches were trapped in the indoor environment and 427 (36%) in the outdoor environment. Three species of cockroaches were identified as B. germanica, B. orientalis and P. americana cockroach. Sixty-nine (66%) of the households used spray or aerosol as a control strategy to reduce the cockroach population.Conclusion: Irrespective of the villages where the cockroaches were trapped, B. germanica was the most prevalent species across the villages. Effective control strategies are required to also reduce the likelihood of pesticide resistance as well as decrease the exposure of humans to pesticide residues. Keywords: Blattella germanica, Blatta orientalis, Periplaneta americana, prevalence, distribution